Highly Flexible and Transparent Polylactic Acid Composite Electrode for Perovskite Solar Cells. Issue 10 (18th August 2020) - Lu, Zheng; Lou, Yanhui; Ma, Peipei; Zhu, Kaiping; Cong, Shan; Wang, Chen; Su, Xiaodong; Zou, Guifu
Abstract : Biomass substrates are urgently needed to develop green electronics. Herein, an ultra‐flexible and transparent biomass‐derived conductive substrate is originated from nature polylactic acid (PLA) with silver nanowires (AgNWs) modified by PH1000. The composite electrode exhibits low sheet resistance of 25 Ω sq −1, high transmittance (over 82% in the region of 400–800 nm), and excellent mechanical durability. After bending tests of 15 000 times at a curvature radius of 3 and 5 mm, the sheet resistances of the composite electrodes only increase to 89 and 51 Ω sq −1, respectively. Biomass electrode–based flexible perovskite solar cells are demonstrated with a champion power conversion efficiency (PCE) of 11.44% and high bending tolerance with preserving over 86% of the initial PCE after 1500 bending cycles at a curvature radius of 5 mm. The biomass electrode exhibits great potential for the development of green flexible devices. Abstract : An ultra‐flexible and transparent biomass‐derived conductive substrate is fabricated from polylactic acid. It exhibits high mechanical durability even when subjected to 15 000 bending cycles. Perovskite solar cells based on the biomass electrodes show good mechanical stability, retaining over 86% of its original power conversion efficiency after bending 1500 times at a curvature radius of 5 mm.